Digital privacy as a currency in the big data ecosystem - Zulhuda, Sonny (2015)
Big Data is where huge data is overconnected and is powered by the digital technology. While the benefit is abundant, there is increasing risk to personal privacy, where one can control what to share and what to keep to himself. Unfortunately, personal information has been overused not only as matter of identification, but also as the commodity and currency.